The Impact of Operating Profit Margin, Debt to Equity Ratio, and Current Ratio on Stock Prices of Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesian Stock Exchange for the Period 2016-2018 - Vivien Ifana Br Ginting; Dita Stefani Nahampun; Khomeiny Yunior (Journal of Research in Business, Economics, and Education, 2023)
This study aims to determine and analyze the impact of the Operating Profit Margin, Debt to Equity Ratio, and Current Ratio of manufacturing companies in the Consumer Goods Industry sector from 2016-2018. The independent variables in this study include the Operating Profit Margin, Debt to Equity Ratio, and Current Ratio, and the dependent variable is the Stock Price. Companies operating in the manufacturing sector of the consumer goods industry are companies with good prospects and are targeted by the public as investment targets. The sampling technique in this study uses purposive sampling with 41 companies sampled using a quantitative method, descriptive research type, explanatory research characteristics, and secondary data type. The population of this study is 51 manufacturing companies in the Consumer Goods Industry sector listed on the Indonesia Stock Exchange from 2016 - 2018. In hypothesis testing, this study uses Multiple Linear Regression Analysis. From the hypothesis testing in this study, it can be concluded that the Operating Profit Margin (OPM), Debt to Equity Ratio (DER), and Current Ratio (CR), which are independent variables, do not significantly influence the Stock Price of consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2016-2018, which is the dependent variable. In addition, the partial hypothesis testing results in this study show that the Operating Profit Margin (OPM) does not significantly affect the Stock Price of consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2016 - 2018, whereas the Debt to Equity Ratio (DER) and Current Ratio (CR) do not significantly affect the Stock Price of consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2016-2018.